PENGARUH PENGGUNAAN MEDIA KOMIK DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMP - Ramadhani, Widya Putri (Jurnal Pendidikan Matematika (JUPITEK), 2019)
This research is a quasi-experimental research with an experimental design aimed at: 1) know the influence of the presentation of material in the form of comic media and without comic media on student mathematics learning outcomes; 2) know the interaction of the presentation of the material with learning motivation towards student mathematics learning outcomes; 3) find out whether the results of learning mathematics students who have high learning motivation and are taught by presenting material in the form of comic media is higher than without using comic media; 4)find out whether the results of learning mathematics students who have low learning motivation and are taught by presenting material in the form of comic media is higher than without using comic media. This research involved all SMP in Kab. Gowa. Determination of the sample is done by selecting an A accredited school, while determining the class as a sampling unit using the Purposive Sampling technique with the selected class having more dominant reading interest. So that class VIIIA was chosen at SMP Neg. 1 Sungguminasa as an experimental class and Class VIIIB in SMP Neg. 4 Sungguminasa as a control class. Variables consist of free variables and bound variables. Free variables presented in the form of a comic media and learning motivation while bound variables using the student maths result. The learning tools developed consists of students book (comic media), students worksheet book (comic media) and lesson plan. The data collected in this study were students 'learning motivation obtained using the learning motivation questionnaire instrument and students' mathematics learning outcomes were obtained using the mathematics learning achievement test instrument. Analysis of student mathematics learning outcomes test results using descriptive analysis and inferential analysis namely ANAVA and independent sample t-test. The results that:1) there is an influence between the presentation of material in the form of comic media and the presentation of material without using comic media on student mathematics learning outcomes; 2) there is no interaction of the presentation of the material with learning motivation on student mathematics learning outcomes; 3) mathematics learning outcomes of students who have high learning motivation and are taught by presenting material in the form of comic media are higher than without using comic media; 4) mathematics learning outcomes of students who have low learning motivation and are taught by presenting material in the form of comic media are higher than without using comic media